(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the life and scholarly legacy of Abu Hanifa al Nuʿman ibn Thabit within the integrated framework of jurisprudence (fiqh) and theology (ʿaqida). The study analyzes Abu Hanifa’s fiqh methodology alongside his theological views, his contribution to the science of kalam, his positions on matters of creed and faith, and the influence his theological school subsequently exercised on the formation of the Maturidi tradition. The article further examines in detail the principal works attributed to Abu Hanifa – “al-Fiqh al-Akbar,” “al-Fiqh al-Absat,” “al-ʿAlim wa-l Mutaʿallim,” “al-Risala,” and “al-Wasiyya” – their chains of transmission (isnad), the scholarly debates surrounding their authenticity, and the history of their manuscripts and printed editions.